Could S-1-based non-platinum doublet chemotherapy be a new option as a second-line treatment for advanced non-small cell lung cancer patients? A multicenter retrospective study - Wang, Xiangling; Wang, Ting; Chu, Yunxia; Liu, Jie; Yi, Cuihua; Yu, Xuejun; Wang, Yonggang; Zheng, Tianying; Cao, Fangli; Qu, Linli; Yu, Bo; Liu, Huayong; et al. (Frontiers in Oncology, 2023)
Background For patients who have contraindications to or have failed checkpoint inhibitors, chemotherapy remains the standard second-line option to treat non-oncogene-addicted advanced non-small cell lung cancer (NSCLC). This study aimed to investigate the efficacy and safety of S-1-based non-platinum combination in advanced NSCLC patients who had failed platinum doublet chemotherapy. Methods During January 2015 and May 2020, advanced NSCLC patients who received S-1 plus docetaxel or gemcitabine after the failure of platinum-based chemotherapy were consecutively retrieved from eight cancer centers. The primary endpoint was progression-free survival (PFS). The secondary endpoint was overall response rate (ORR), disease control rate (DCR), overall survival (OS), and safety. By using the method of matching-adjusted indirect comparison, the individual PFS and OS of included patients were adjusted by weight matching and then compared with those of the docetaxel arm in a balanced trial population (East Asia S-1 Trial in Lung Cancer). Results A total of 87 patients met the inclusion criteria. The ORR was 22.89% (vs. 10% of historical control, p < 0.001) and the DCR was 80.72%. The median PFS and OS were 5.23 months (95% CI: 3.91–6.55 months) and 14.40 months (95% CI: 13.21–15.59 months), respectively. After matching with a balanced population in the docetaxel arm from the East Asia S-1 Trial in Lung Cancer, the weighted median PFS and OS were 7.90 months (vs. 2.89 months) and 19.37 months (vs. 12.52 months), respectively. Time to start of first subsequent therapy (TSFT) from first-line chemotherapy (TSFT > 9 months vs. TSFT ≤ 9 months) was an independent predictive factor of second-line PFS (8.7 months vs. 5.0 months, HR = 0.461, p = 0.049). The median OS in patients who achieved response was 23.5 months (95% CI: 11.8–31.6 months), which was significantly longer than those with stable disease (14.9 months, 95% CI: 12.9–19.4 months, p < 0.001) or progression (4.9 months, 95% CI: 3.2–9.5 months, p < 0.001). The most common adverse events were anemia (60.92%), nausea (55.17%), and leukocytopenia (33.33%). Conclusions S-1-based non-platinum combination had promising efficacy and safety in advanced NSCLC patients who had failed platinum doublet chemotherapy, suggesting that it could be a favorable second-line treatment option.